Réponse à Joëlle Aden : le corps à la lumière de l’émergentisme linguistique. - Grégory Miras (Recherches en didactique des langues et des cultures)
In her paper, Joëlle Aden considers the implementation of an enactive approach which would participate in defining the contours of a first-person experienced method of exploration. We will try to question this framework by analyzing how the body is theorized in linguistic emergentism. We will reconsider her epistemological analysis which led her to acknowledge we are INSIDE language. We will follow her proposition for an epistemological shift in the field of education and applied linguistics while considering, with hindsight, the possibility of generalizing such a framework.